Pemberdayaan Petani Melalui Pelatihan Kewirausahaan Berbasis Pangan Lokal di Desa Tes Kecamatan Bikomi Utara Kabupaten Timor Tengah Utara - Mardit N.Nalle; Anna Tefa; Emilia K.Kiha (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Local food-based Entrepreneurship Training will be one of the important things for the community in utilizing products. However, there are several major problems in the Production sector such as the continuity of local food products not being available at all times because the community does not utilize raw products to be processed into new products that have added value. In addition, there are problems in the managerial and marketing fields. The problems in the managerial field are lack of planning, organization, lack of organization, lack of directors in the division of work in groups and lack of supervision. In the marketing field, there are still problems in promoting and selling products where in addition the products have not been accepted by the Community. The method of implementing Community Service activities from the UNIMOR Research and Community Service Institute (LPPM) provides solutions in answering the problems that exist in the Kasih Setia Women Farmers group. The method of implementing the activities in question is by identifying problems using the Participatory Rural Appraisal (PRA) model. The results achieved are that Farmers gain Knowledge in the Empowerment Program through Entrepreneurship Training activities by changing Purple Sweet Potato and Yellow Pumpkin materials into pumpkin sticks and purple sweet potato sticks so that they have added value to the product. There are several suggestions that need to be considered in empowering the Kasih Setia Farmer group, namely that Farmer Empowerment activities must continue to be encouraged in other villages or in the village with an empowerment model in the form of other processed foods to increase farmers' knowledge in processing local products into new products so that the added value of the product becomes higher to penetrate the market.